COMMENTARY ON "MOVING THROUGH ADOLESCENCE: DEVELOPMENTAL TRAJECTORIES OF AFRICAN AMERICAN AND EUROPEAN AMERICAN YOUTH". Issue 4 (11th November 2017) - Smetana, Judith G.
Abstract : This commentary discusses Gutman et al.'s monograph on developmental trajectories of African American and European American youth. Conceptual and methodological strengths of the monograph are highlighted, and the historical context of the study, including societal and technological changes that have altered the experience of adolescence and advances in developmental science that have occurred since the MADICS was conducted, are discussed. Finally, several suggestions are offered for ways Gutman et al.'s analyses could be elaborated to address further questions about adolescent development in context.